Structural dynamics and crack propagation behaviour under uniform and non-uniform temperature conditions. - Kamei, Khangamlung (Cranfield University, 2022)
The robustness and stability of machinery depend on structural integrity. This stability is, however, compromised by aging, wear and tear, overloads, and environmental factors. A study of vibration and fatigue crack growth for structural health monitoring is one of the core research areas in recent times. The research is yet to input sufficient explanations about the dynamic behaviour of the structure under distributed temperature. The structural dynamics can be influenced by material microstructure, temperature distribution, and duration of exposure to the thermal environment. The applied temperature can cause significant variations in the modal response. The existing studies are limited concerning temperature change and compel extensive investigation in a crack and uncracked condition. In this research, the structural dynamics and fatigue crack propagation behaviour when subjected to thermal and mechanical loads have been studied. It investigates the modal parameters of uncracked and various cracked specimens under uniform and non-uniform temperature conditions. An analytical model considering the effective length of the beam is developed to analyse the modal response of the beam. Then, the model is modified to enumerate the modal behaviour of the beam in the presence of crack. The model is validated by experimental and numerical approaches. The experimental evaluation is conducted by considering three heating rates to attain the required temperatures. In the first case, ramping at 2°C/min is assumed as a slow heating rate. While ramping at 5°C/min and 8°C/min are assumed as moderate and rapid heating rates respectively. The heating rates are considered to compare the structural response changes. A small variation on modal parameters is noticed for different heating rates and when the applied uniform temperatures are changed to non-uniform temperatures, especially at elevated temperatures. This signifies heating at different rates has a slight effect while measuring the dynamic response of any mechanical system. The results showed that changes in modal parameters of the beam are associated with the change in temperatures and heating rate. Furthermore, this research substantiates the fatigue crack propagation behaviour of pre-seeded cracks. The propagated crack depths are measured based on pixels contains in the crack. It is found that propagated crack depends on applied temperatures and associated mass. The appearance of double crack fronts and multiple cracks are observed. The multiple crack appearance seems due to the selection of pre-seeded crack shapes. Hence, the real crack and pre- seeded crack are distinct and need careful consideration in crack propagation evaluation.
Keywords: Modal Parameters; Fatigue Crack; Crack Depth Measurement; Fracture Mechanics; Vibration Analysis; Temperature Distribution